Transcription termination by nuclear RNA polymerases - Richard, Patricia (Cold Spring Harbor Laboratory Press, 2009)
Gene transcription in the cell nucleus is a complex and highly regulated process. Transcription in eukaryotes requires three distinct RNA polymerases, each of which employs its own mechanisms for initiation, elongation, and termination. Termination mechanisms vary considerably, ranging from relatively simple to exceptionally complex. In this review, we describe the present state of knowledge on how each of the three RNA polymerases terminates and how mechanisms are conserved, or vary, from yeast to human.